Off‐Board Trading of NYSE‐Listed Stocks: The Effects of Deregulation and the National Market System - HAMILTON, JAMES L. (Journal of Finance, 1987)
ABSTRACT An econometric time‐series model of off‐board trading of NYSE‐listed stocks shows that high NYSE commission rates were an incentive for third‐market trading but that trading on the regional exchanges, which is most of the off‐board trading, has been affected very little by commissions or their deregulation. The effects of some changes in the trading organization and rules are estimated, including several that are part of the emerging National Market System. The estimates imply that the NMS has increased competition for the NYSE, as Congress intended, and has prompted the NYSE to improve its performance to retain market share.